Education and Social Media : Toward a Digital Future - Agur, Colin; Sonnevend, Julia; Greenhow, Christine (Book collections on Project MUSE., 2016)
How are widely popular social media such as Facebook, Twitter, and Instagram transforming how teachers teach, how kids learn, and the very foundations of education? What controversies surround the integration of social media in students' lives? The past decade has brought increased access to new media, and with this, new opportunities and challenges for education. In this book, leading scholars from education, law, communications, sociology, and cultural studies explore the digital transformation now taking place in a variety of educational contexts. The contributors examine such topics as social media usage in schools, online youth communities, and distance learning in developing countries; the disruption of existing educational models of how knowledge is created and shared; privacy; accreditation; and the tension between the new ease of sharing and copyright laws. Case studies examine teaching media in K-12 schools and at universities; tuition-free, open education powered by social media, as practiced by University of the People; new financial models for higher education; the benefits and challenges of MOOCS (Massive Open Online Courses); social media and teacher education; and the civic and individual advantages of teens' participatory play.